DNA damage burden causes selective CUX2 neuron loss in neuroinflammation - Laura Morcom; Wenlong Xia; Zhaoyang Xu; Yashika Awasthi; Celine Geywitz; Matthew O. Ellis; Tomas Noli; Amel Zulji; Daniel Yamamoto; Gemma C. Girdler; Li Kai; Keying Zhu; et al. (Nature, 2026)
Abstract Neurodegeneration shows regional and cell-type-specific patterns in ageing and disease 1 , but the underlying mechanisms for cell-type-specific neuronal losses remain poorly understood. Previous studies have shown that upper cortical layer thinning occurs in progressive human multiple sclerosis (MS) and that cortical layer 2 and layer 3 (L2/3) excitatory neurons (L2/3ENs) that express CUT-like homeobox 2 ( CUX2 ) are selectively vulnerable to degeneration 2 . Here we report that L2/3ENs within MS cortical lesions have an elevated DNA damage burden. DNA damage and selective loss of L2/3ENs were recapitulated in diverse mouse models of demyelination and pan-cortical inflammation, confirming their intrinsic vulnerability. Functions of Cux2 and activating transcription factor 4 ( Atf4 ) were essential for resilience of L2/3ENs during postnatal neuroinflammation, acting in neurons to enhance DNA double-strand break repair. Interferon-γ, a cytokine implicated in MS pathogenesis 3,4 , was sufficient to elevate levels of reactive oxygen species, leading to DNA damage-mediated neuronal death in vitro, and caused selective depletion of L2/3 neurons in mice. These findings indicate that DNA damage burden and inadequate repair in CUX2 + L2/3ENs contributes to selective vulnerability in neuroinflammatory injury.